Interlaminar fracture of multidirectional glass/epoxy laminates under mixed-mode I + II loading - Morais, A.B. de
The mixed-mode I + II interlaminar fracture of multidirectional glass/epoxy laminates is investigated. Mixed-mode bending (MMB) tests were performed on specimens with delaminations in 0/theta-type interfaces, with theta varying from 0 to 90 degrees. Preliminary three-dimensional finite-element analyses validated the beam theory model (BTM) used for analysing experimental data. The compliances measured are in a good agreement with BTM predictions. The total critical energy release rate GC varies linearly with the mode II ratio G(II)/G, although some discrepancies are observed in the high-mode II results for the 0/45 and 0/90 specimens.